Diversity of Phytophthora affecting Horticultural crops in India - ANANDARAJ, M. (Indian Phytopathology, 2012)
The genus Phytophthora with over one hundred species is one of the most destructive among plant pathogens. Species of Phytophthora occur in various ecosystems including agricultural and non agricultural systems and rain forests. They attack various plant parts and are responsible for the severe economic losses of various agricultural and horticultural crops. Ever since the genus was erected after the notorious Irish famine due to late blight of potato, several plant pathogenic species have been described, the latest being P. ramorum causing oak wilt in pacific coast of the United States of America and P. kernoviae on forest trees and ornamentals in UK (Brasier et al., 2005). Species of the genus Phytophthora were reviewed by Erwin & Ribeiro (1996) in the book ‘Phytophthora worldwide’, which included 59 species with five varieties. Since then, several new Phytophthora species have been described from different parts of the world and now over one hundred species are described (Sikora et al., 2012). Most of the species of the genus have a wider host range, for example, over 2000 plant species are thought to be susceptible to infection by P. cinnamomi in Australia, where this pathogen has severely altered native plant communities since its accidental introduction in the 1920s (Hardham, 2005). There are also some species with a narrow host range such as P. sojae and P. infestans. In India P. palmivora infects several horticultural crops such as palms, cocoa, citrus, black pepper and cassava. Due to their significance and economic importance, there has been increasing interest in the molecular genetics and genomics of Phytophthora species. In spite of best efforts by scientists all over the world, the pathogen is threatening to re-emerge breaching all barricade put up as host resistance and other management strategies against late blight of potato and tomato (Fry and Goodwin 1997; Kamoun, 2001). Their ability to survive has been tremendous due to the emergence of new races. The genetic recombination occurs not only by sexual recombination but also through parasexual recombination. The pathogens of this genus affect most of the cultivated crops in a wide range of agro climatic regions affecting both horticultural and field crops in India in different agro-climatic zones (Table 1). The wet monsoon period prevailing over various parts of the country provides ideal conditions for them to infect. In perennial crops like apple, citrus, black pepper the damage caused to the below ground portions such as roots and collar is expressed later in the season. The expression of symptoms depends up on the site of infection and extent of damage. Though, many crops are affected by Phytophthora in India, only some of the diseases are well investigated. There are new diseases caused by Phytophthora in field crops such as cassava that threaten the cultivation of these crops.